The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/ismej.2009.83
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of archaeal and bacterial diversity in fermented seafood using barcoded pyrosequencing

Abstract: Little is known about the archaeal diversity of fermented seafood; most of the earlier studies of fermented food have focused on lactic acid bacteria (LAB) in the fermentation process. In this study, the archaeal and bacterial diversity in seven kinds of fermented seafood were culture-independently examined using barcoded pyrosequencing and PCR-denaturing gradient gel electrophoresis (DGGE) methods. The multiplex barcoded pyrosequencing was performed in a single run, with multiple samples tagged uniquely by mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
164
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(179 citation statements)
references
References 81 publications
12
164
0
2
Order By: Relevance
“…A rarefaction curve with no plateau indicated the need for additional sampling to reveal the extent of ecosystem diversity Sequences classified as Crenarchaeota, Chlamydiae, Spirochaetes, BRC1, Armatimonadetes, Nitrospira, TM7, Tenericutes, Synergistetes, WS3, Caldiserica, Cyanobacteria, Euryarchaeota, Elusimicrobia, Fusobacteria, Thermodesulfobacteria, Chlorobi, DeinococcusThermus and unclassified phyla were summarized in the group of "other" phyla. (Roh et al, 2010). In this study, all rarefaction curves failed to reach saturation (Fig.…”
Section: Diversity Of Microbial Communitymentioning
confidence: 49%
“…A rarefaction curve with no plateau indicated the need for additional sampling to reveal the extent of ecosystem diversity Sequences classified as Crenarchaeota, Chlamydiae, Spirochaetes, BRC1, Armatimonadetes, Nitrospira, TM7, Tenericutes, Synergistetes, WS3, Caldiserica, Cyanobacteria, Euryarchaeota, Elusimicrobia, Fusobacteria, Thermodesulfobacteria, Chlorobi, DeinococcusThermus and unclassified phyla were summarized in the group of "other" phyla. (Roh et al, 2010). In this study, all rarefaction curves failed to reach saturation (Fig.…”
Section: Diversity Of Microbial Communitymentioning
confidence: 49%
“…Neither Sanger nor next-generation sequencing is able to circumvent potential biases introduced by PCR, because they are all based on PCR. In this study, due to the difficulty of extracting DNA from coal and rock samples, we have used nested PCR to amplify the 16S rRNA gene, which is also used to analyze the microbial communities in fermented seafood by pyrosequencing (Roh et al, 2009). Although nested PCR might introduce more potential bias and mask actual microbial diversity, it has been reported that more microbial diversity was found using nested PCR compared to direct PCR (Vissers et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent advances in massively parallel, short-amplicon sequencing technologies have launched a breakthrough in microbial ecology studies of wine-and foodfermentation systems (14,(21)(22)(23)(24)(25)(26)(27), putting hitherto untenable ecological questions within reach.…”
Section: Significancementioning
confidence: 99%